2022
DOI: 10.7150/ijbs.76162
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived extracellular vesicles inhibit ferroptosis and promote distant metastasis of nasopharyngeal carcinoma by upregulating ITGB3

Abstract: Nasopharyngeal carcinoma (NPC) is a malignancy with high metastatic and invasive nature. Distant metastasis contributes substantially to treatment failure and mortality in NPC. Platelets are versatile blood cells and the number of platelets is positively associated with the distant metastasis of tumor cells. However, the role and underlying mechanism of platelets responsible for the metastasis of NPC cells remain unclear. Here we found that the distant metastasis of NPC patients was positively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…For instance, cell ferroptosis is suppressed in osteosarcoma by recombinant lysine specific demethylase 4A (KDM4A)-mediated demethylation of the solute carrier family 7 member 11 (SLC7A11) histone, which deepens the response to osteosarcoma, chemoresistance, and understanding of epigenetic regulatory mechanisms in metastasis ( 23 ). Also, inhibiting ferroptosis and promoting distant metastasis of nasopharyngeal cancer by upregulating integrin subunit beta 3 (ITGB3) are two effects of platelet-derived extracellular vesicles ( 24 ). Moreover, dysregulation of cholesterol homeostasis leads to resistance to ferroptosis, increasing cancer tumorigenicity and metastasis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cell ferroptosis is suppressed in osteosarcoma by recombinant lysine specific demethylase 4A (KDM4A)-mediated demethylation of the solute carrier family 7 member 11 (SLC7A11) histone, which deepens the response to osteosarcoma, chemoresistance, and understanding of epigenetic regulatory mechanisms in metastasis ( 23 ). Also, inhibiting ferroptosis and promoting distant metastasis of nasopharyngeal cancer by upregulating integrin subunit beta 3 (ITGB3) are two effects of platelet-derived extracellular vesicles ( 24 ). Moreover, dysregulation of cholesterol homeostasis leads to resistance to ferroptosis, increasing cancer tumorigenicity and metastasis ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that PEVs from NPC patients induced the metastasis of NPC cells by upregulating ITGB3 expression. Upregulating ITGB3 increased SLC7A11 expression by activating the MAPK/ERK/ATF4/Nrf2 axis and enhancing protein stability, that suppressed ferroptosis, therefore promoting the distant metastasis of NPC cells 42 . Many other studies also shown that PEVs could transfer to target cells and their cargoes promoted phenotypic changes and novel functions of target cells which influenced the progression of tumor 43 .…”
Section: Evs Affect Various Processes Of Npcmentioning
confidence: 96%
“…Moreover, other processes such as tumour progression and metastasis can also be affected by non-tumour-derived exosomes [ 194 , 195 , 196 ]. Although there are some novel studies on the effects of exosomes derived from endothelial cells and platelets on metastasis and therapy resistance in NPC, such work is limited [ 197 , 198 ]. In future studies of NPC, it is important to diversify these directions and avoid an excessive focus solely on TEX.…”
Section: Limitations Of Exosomes In Clinical Use and Future Directionsmentioning
confidence: 99%